Design and Validation of a Competency Assessment for Electrical Power Systems in Engineering Education - Adi Sutopo; Arif Rahman; Dadang Mulyana (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to design, develop, and validate a competency test for assessing students in the Electric Power System field. Given the need for rigorous, competency-based assessments in Electrical Engineering, this study addresses the gap by creating a test aligned with specific graduate competencies. The competency test was developed using the Borg and Gall development model, following seven systematic steps. Test items were structured around the competencies expected of graduates from the Electrical Engineering program, categorized according to Bloom’s taxonomy levels 4, 5, and 6 to assess higher-order cognitive skills. A two-phase trial was conducted with 80 students to refine and validate the test. Validation by material and evaluation experts rated the test highly feasible, with scores of 71.0 and 45.55, respectively. Empirical validity testing, using biserial correlation, confirmed that all items were valid (correlation 0.302), and the reliability test via KR-20 yielded a high reliability coefficient (α = 0.854). Item difficulty was balanced, with 10% easy, 83% moderate, and 0.7% difficult questions. Item discrimination levels were 20% moderate, 33% good, and 47% very good. The results suggest that the competency test is a reliable and valid tool for assessing critical competencies in Electric Power Systems, effectively distinguishing between different levels of student ability. This validated competency test provides a robust assessment tool, supporting competency-based education in Electrical Engineering. Its design and validation process can serve as a model for future competency assessments in technical disciplines.